Psychological study of the impact of computer technology and the Internet on the development of adolescent consciousness and thinking - Jumaev Ulugbek Sattorovich (Genius Journals, 2021)
In the current process of globalization, it is important to avoid attacks on the consciousness of the individual, to form a strong spirituality in everyone's mind, to protect young people from destructive groups, to create in the minds of every citizen of our society ideological immunity, anti-manipulative, assertive behavior based on our national and spiritual values. is one of the most pressing issues. This scientific article discusses the destructive factors affecting the minds of adolescents and the social psychological mechanisms of their elimination.
Keywords: Globalization; Anti-Manipulative; Assertive Behavior; Psychological Mechanisms